السّمات الأسلوبية للأسلوب القرآني - زواري, أحمد علي (جامعة الوادي - University of Eloued, 2019)
في بحثنا هذا تحدثنا عن الأسلوب القرآني المعجز الذي تحدى الله تعالى به العرب على أن يأتوا بمثله، وقد ركزنا فيه على أهم السمات الأسلوبية البارزة التي تميز بها الأسلوب القرآني عن غيره من أساليب العرب وفنها القولي، ونظرا لسعة الموضوع وتشعب أطرافه وثراه المعلوماتي فقد أجملنا القول في ثلاث سمات بارزة وهي: الجمالية في التعبير، والدقة في التصوير، والقوة في التأثير، فكانت هذه العناصر الثلاث هي محور الحديث في بحثنا، وقد دعمناها بنماذج مختصرة من القرآن الكريم - بحسب ما تسمح به صفحات البحث - لتبيّن كل واحدة منها السمة المراد بيانها، وخلصنا في الأخير لبعض النتائج والتي منها: أن هناك العديد من السمات الأسلوبية التي تميز بها الأسلوب القرآني، وما ذكرناه منها فهي مجملة في عناصر كليه يمكن أن تكون كل واحدة منها بحثا مستقلا وتفصل في جزئياتها وفروعها. In our research we talked about the miraculous Qur’anic method with which God Almighty challenged the Arabs to come up with a similar one, and we focused in it on the most important stylistic features that distinguish the Qur’anic style from other Arab methods and its legal art. There are three distinct features, namely: aesthetics in expression, accuracy in impersonation, and power in influence.These three elements were the focus of the conversation in our research, and we have supported them with brief examples from the Holy Qur’an - according to what the research pages allow - to show each of them the feature to be explained Finally, we concluded some results, including: That there are many stylistic features that characterize the Qur’anic style, and what we mentioned of them are summed up in the elements of a whole, each of which can be an independent research and separate its parts and branches.
مقال
Keywords: السمات؛ السمة؛ الأسلوب القرآني؛ التصوير، التعبير; Features ; Attribute ; Quranic style ; impersonation; expression.